The Application of Cooperative Learning Model Think Pair Share (TPS) Type to Improve The Ability of Understanding Science Concepts in Primary School - Sumiati, Tati; Hendawati, Yuyu; Caturiasari, Jennyta; Yulianingsih, Meli (International Conference on Elementary Education, 2020)
This research is based by the ability to understand students' science concepts that are still low.This is indicated by the average score of students below the KKM of 51.52. Where as KKM is applied in schools, namely 70. The ability to understand students' science concepts is still low because the teacher has not applied a model that is in accordance with the theme of Lingkungan Sahabat Kita. The purpose of this study was to improve the understanding of students' science concepts by applying a cooperative learning model of think pair share (TPS) type. Research method used in this study was Classroom Action Research (CAR) three cycles research. The research subjects were fifth grade students of Karya Mekar Elementary School totaling 33 students. Based on the indicators of understanding ability used in this study, namely interpreting, explaining, giving examples and concluding. The indicator concluded that in the first cycle, the percentage was 34.3%. Then in cycle II it increased to 54.5% and in cycle III it increased to 81.1%. Based on the results of the study it can be concluded that the application of cooperative learning models of think pair share types can improve the understanding of students science concepts in elementary schools